Systematic review of surface disinfection: Spraying versus wiping for COVID-19 prevention - Babasola 0. Okusanya; Muzzammil Gadanya; Anthony Nlemadim; Victoria Adaramoye; David O. Akeju; John Ehiri; Martin M. Meremiku (Journal of Public Health in Africa)
Background: Within countries, community spread of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) propagated the infection despite the use of non-pharmaceutical interventions.